Upaya Penyelesaian Sengketa atas Gagalnya Pengisian Saldo (Top Up) yang dialami Pengguna Kartu Tap Cash Bank Negara Indonesia - Rahmadi Indra Tektona; Mardi Handono; Regina Yurisprastita Jufri (Universitas Medan Area, 2020)
Writing aims to find out the effort to resolve disputes for Tap Cash BNI card users who have failed to top up, which results in losses to consumers. The focus of the problem is how to resolve disputes between the banks as Tap Cash card issuers and consumers of electronic money users. This research begins by reviewing various laws and regulations which form the basis of legal protection for card users, for this reason, it is used normative juridical research, by reviewing the applicable laws and regulations. the author also uses the concept of the rule of law which is obliged to provide legal guarantees. In the matter of efforts to resolve disputes for consumers using the BNI Tap Cash card, the concept of legal protection also applies based on the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection and Financial Services Authority Regulation Number: 1 / POJK.07 / 2013 concerning Consumer Protection of the Financial Services Sector. Analysis of legal materials used is the analysis of legal materials with a deductive method which is a research method based on general concepts to provide concrete explanations of specific legal issues, data is collected through seminars, articles, and interviews and analyzed qualitatively. Based on the results of research conducted on the problem, it was found several forms of settlement efforts provided by the BNI bank namely the resolution of disputes outside the court and the resolution of disputes through the court.